Design and Pilot Results of a Mobile Phone Weight-Loss Application for Women Starting a Meal Replacement Programme. (April 2013) - Brindal, Emily; Hendrie, Gilly; Freyne, Jill; Coombe, Mac; Berkovsky, Shlomo; Noakes, Manny
We developed and tested a mobile phone application (app) to support individuals embarking on a partial meal replacement programme (MRP). Overweight or obese women were randomly allocated to one of two study groups. The intervention group received an MRP Support app. The control group received a static app based on the information available with the MRP. A total of 58 adult women (Support n = 28; Control n = 30) participated in the 8-week trial. Their BMI was 26-43 kg/m 2 . Usage data suggested that the intervention group were more engaged with using the app throughout the study period. Mixed modelling revealed that the difference in weight loss between the intervention and control groups (estimated mean, EM = 3.2% and 2.2% respectively) was not significant ( P = 0.08). Objective data suggested that users of the Support app were more engaged than those using the control app. A total of 1098 prompts (54%) asking people in the intervention group to enter their meals were completed prior to the evening prompt. Women in the intervention group reported a greater increase in positive affect (i.e. mood) than those in the control group (EM = 0.48 and −0.01, respectively) ( P = 0.012). At Week 8, those in the control group reported a greater decrease in the effort they were willing to put into staying on the diet than those who received the Support app (EM = −2.8 and −1.4, respectively) ( P = 0.024). The Support app could be a useful adjunct to existing MRPs for psychological outcomes.